A comparison of physical education curriculum between Chinese and American higher education institutes - Li, G.; Zhu, Z. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This paper compares and contrasts the physical education curriculum between Jiang Han University (Wuhan, China) and University of Missouri- Columbia (America), and suggests ways to improve the college physical education curriculum in China. Methods An analysis of the literature was conducted. Archived physical education curriculum material was collected at the University of Missouri- Columbia and used for comparison with archival material collected in China. A survey instrument was designed and administered to American university students.